PEMBUATAN PETA SITUASI DUSUN CUNGKRUNGAN KELURAHAN BELUK KECAMATAN BAYAT KABUPATEN KLATEN PROPINSI JAWA TENGAH - , ANISSA JATU R ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Take measurements of an area by specifying the elements (distance and angle) or the points of existing buildings in the area that in sufficient quantities, so from that area the contents can be made fairly clear picture with a scale that has determined in advance. Mapping procedure done with semidigital method, that is the measurement or data collection processes by using a Total Station and Waterpass, the measurement results of data processing and data presentation performed digitally by using the software. The result is a map that describes the condition of the field situation (Cungkrungan Village, Beluk Village, Bayat Sub-District, Klaten District, Central Java Province) at 1:500 scale in UTM projection system (Universal Transverse Mercator).